(untitled) (Educational Perspectives Magazine (REPED), 2023)
For the present study, the authority is understood as the action that exerts the teacher to obtain that the students accept their demands and resign themselves to other possibilities of action that could be equally attractive. The main objective of this investigation is to characterize the forms in which the teachers exert authority from the point of view of their students. We examined the reasons given by the students to explain why they obey some of their teachers. The sample is constituted by 415 students of the second year of secondary education. These students come from lower-middle class socioeconomic sectors of Santiago, Chile. The content analysis we carried out identified five ways in which the teachers exert authority: a) by means of moral exigency; b) by means of the generation of loyalties and affective bonds; c) by means of the fear of the discretionary power; d) by means of a rigorous and demanding education; e) by means of the right and implacable application of the rules of the establishment. The study concludes with a discussion of these results and the challenges that present these kinds of authority for the learning opportunities of the students.